Aspiration Thrombectomy in a Patient with Suprarenal Inferior Vena Cava Thrombosis - Hideyuki Kishima; Masashi Fukunaga; Kunihiko Nishian; Ten Saita; Tetsuo Horimatsu; Masataka Sugahara; Takanao Mine; Tohru Masuyama (Case Reports in Cardiology)
DVT has rarely been observed in the inferior vena cava (IVC). Pulmonary embolism (PE), which can be life-threatening, often occurred in patients with IVC thrombosis. Therefore, an IVC filter is frequently used in those patients for the prevention of PE. A case of successful endovascular treatment of an IVC thrombus in a patient with relative contraindications to implantation of an IVC filter is presented. This case report shows that aspiration of thrombi caught in the removable IVC filter may be an alternative to surgery in high-risk patients with catheter-related suprarenal inferior vena cava thrombosis.